Trends and variation in repeat neuroimaging for children with traumatic intracranial hemorrhage - Pradip P. Chaudhari; Jose A. Pineda; Richard G. Bachur; Robinder G. Khemani (Journal of the American College of Emergency Physicians Open)
Abstract Objectives We aimed to determine trends and institutional variation in repeat neuroimaging in children with traumatic intracranial hemorrhage and to identify factors associated with neuroimaging modality (subsequent magnetic resonance imaging [MRI] vs computed tomography [CT]). Methods We conducted a retrospective cross‐sectional study of 35 hospitals in the Pediatric Health Information System database. We included children <18 years of age hospitalized from 2010–2019 with intracranial hemorrhage and who underwent a brain CT. We calculated repeat neuroimaging rates by modality and used regression analyses to examine temporal trends. We used hierarchical logistic regression to identify factors associated with subsequent MRI versus repeat CT, controlling for hospital. Results We identified 12,714 children with intracranial hemorrhage, of which 5072 with repeat neuroimaging were studied. Of the 5072 children with repeat neuroimaging, repeat CT was performed in 67.6% (n = 3429) and subsequent MRI in 32.4% (n = 1643). Overall repeat neuroimaging with either a CT or MRI remained similar from 2010–2019 (P = 0.431); however, repeat CT scans significantly decreased (P = 0.001); whereas, MRIs significantly increased (P < 0.001). Repeat neuroimaging by hospital ranged from 20%–80%. After controlling for institution, subsequent MRI was more likely to be used in younger children and children who did not receive hyperosmotic agents, neurosurgical interventions, or intensive care unit admission (all P‐values <0.001). Conclusions We found that repeat neuroimaging rates for children with intracranial hemorrhage vary substantially by institution. We also found that although MRI was increasingly used to re‐image these children, overall repeat neuroimaging rates (CT or MRI) have not decreased over the past decade. Future work to implement optimal utilization of neuroimaging in these children is needed.